PEREKAYASAAN MODEL PEMBELAJARAN MEMBACA PERMULAAN DI SEKOLAH DASAR BERBASIS PENGEMBANGAN SIKAP, KETERAMPILAN, DAN PENGETAHUAN - Ernalis, -; Syahruddin, Didin (Universitas Pendidikan Indonesia, 2017)
Abstract: The research objective to be achieved through the second year the study was to determine, explain, and explain (1) the prototype model of learning to read beginning in early elementary school classes in accordance with the needs of teachers and students current conditions based on the results of the validation test; (2) the contribution of the implementation of Early reading learning model-based development of attitudes, skills and knowledge to the development of students' skills in reading starters based on the results of the validation test; (3) the contribution of the implementation of Early reading learning model-based development of attitudes, skills and knowledge to primary school students' knowledge acquisition thematically based on the results of the validation test. This research was conducted using the method of Research and Development (R D). The subjects were teachers and students of primary schools in the district and sub-district Cileunyi Ujungberung Bandung Regency Bandung. Research data will be collected using several instruments. Research data will be processed using data processing techniques of qualitative and quantitative data processing techniques with statistical test. Based on the results of the study concluded that the learning model based SKP Early reading can be used effectively to improve student reading skills beginning. The second conclusion is that the learning model based SKP Early reading can be used effectively in improving students' attitudes Early reading. Based on this fact, the model can be used in schools as an alternative model of learning to read in low grade.Keywords: SKP models, read the beginning, the attitude of reading, low gradeÂ Abstrak: Tujuan penelitian yang hendak dicapai melalui penelitian tahun kedua adalah untuk mengetahui, menjelaskan, dan memaparkan (1) prototipe model pembelajaran membaca permulaan di kelas awal sekolah dasar yang sesuai dengan kebutuhan guru dan kondisi siswa saat ini berdasarkan hasil uji validasi; (2) kontribusi penerapan model pembelajaran membaca permulaan berbasis pengembangan sikap, keterampilan, dan pengetahuan terhadap perkembangan keterampilan siswa dalam membaca permulaan berdasarkan hasil uji validasi; (3) kontribusi penerapan model pembelajaran membaca permulaan berbasis pengembangan sikap, keterampilan, dan pengetahuan terhadap perolehan pengetahuan siswa sekolah dasar secara tematis berdasarkan hasil uji validasi. Penelitian ini dilaksanakan dengan menggunakan metode Penelitian dan Pengembangan (RD). Subjek penelitian ini adalah guru dan siswa sekolah dasar di Kecamatan Cileunyi Kabupaten Bandung dan Kecamatan Ujungberung Kota Bandung. Data Penelitian akan dikumpulkan dengan menggunakan beberapa instrumen. Data hasil penelitian akan diolah dengan menggunakan teknik pengolahan data kualitatif dan teknik pengolahan data kuantitatif dengan uji statistika. Berdasarkan hasil penelitian disimpulkan bahwaÂ model pembelajaran membaca permulaan berbasis SKP dapat digunakan secara efektif dalam meningkatkan kemampuan membaca permulaan siswa. Simpulan yang kedua adalah bahwa model pembelajaran membaca permulaan berbasis SKP dapat digunakan secara efektif dalam meningkatkan sikap membaca permulaan siswa. Berdasarkan kenyataan tersebut, model yang dikembangkan dapat digunakan di sekolah sebagai salah satu alternatif model pembelajaran membaca di kelas rendah.Kata Kunci: model SKP, membaca permulaan, sikap membaca, kelas rendah